Catechins and lignan from the flower buds of Rosa chinensis Jacq. (August 2020) - Liu, Ying; Lu, Zhao; Wang, Mei; Chen, Yang; Zhan, Rui; Shao, Li-Dong; Chen, Ye-Gao
Graphical abstract: Highlights: The flower buds of Rosa chinensis Jacq. were investigated. Five catechins (1-5 ) and a lignan (6 ) were isolated. Rosacatechin A (1 ) is a catechin analogue with 8- n- butoxycarbonyl substitution. The absolute configuration of 1 was determined as 2 R, 3 S . Abstract: Five catechins (1 -5 ) including a new compound rosacatechins A (1 ) and a new natural product (2 ), along with a lignan (6 ) were isolated from 70% aqueous acetone extracts of the flower buds of Rosa chinensis Jacq. Their structures were elucidated by extensive spectroscopic analysis. No cytotoxicity was detected on the anti-proliferative assay of these compounds against five cancer cell lines.